Acceptance and Content of Iron of Nahukol (Broccoli Tofu Nugget) as an Alternative Food to Prevent Anemia - Andika Ananda Eka Putra; Juliana Cristyaningsih; Mujayanto; Nurul Hindaryani (Politeknik Kesehatan Kemenkes Surabaya, 2023)
Anemia is a condition of low red blood cell mass or hemoglobin. Another way of prevention and control is to consume food sources of iron such as tofu. The general objective of this study was to determine the characteristics of